Negative electrode active material layer, and solid-state battery
Patent Information
- Application Number
- JP2025060698
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-04-01
- Publication Date
- 2026-10-14
AI Technical Summary
【0007】 本開示によれば、電池の放電レート特性を改善することができる負極活物質層、及びそのような負極活物質層を有する固体電池を提供することができる。
Smart Images

Figure 2026167228000001_ABST
Abstract
Description
[Technical Field]
[0001] This disclosure relates to a negative electrode active material layer and a solid-state battery. [Background technology]
[0002] As disclosed in Patent Documents 1 and 2, a negative electrode active material layer containing a lithium alloy is known. [Prior art documents] [Patent Documents]
[0003] [Patent Document 1] Japanese Patent Publication No. 2020-184407 [Patent Document 2] Japanese Patent Publication No. 2024-141459 [Overview of the Initiative] [Problems that the invention aims to solve]
[0004] The disclosing parties in this case have found that there is room for improvement in the discharge rate characteristics of batteries having a negative electrode active material layer containing a lithium alloy.
[0005] This disclosure aims to provide a negative electrode active material layer that can improve the discharge rate characteristics of a battery, and a solid-state battery having such a negative electrode active material layer. [Means for solving the problem]
[0006] The Disclosing Party has found that the above-mentioned problems can be solved by the following means. <Aspect 1> At a discharge depth of 80%, the lithium alloy is represented by the general formula Li-X, where X is Mg, Ag, or a combination thereof, and The degree of crystallinity of Li in the lithium alloy, as determined by XRD analysis, is 8.0% or less, where the degree of crystallinity is given by the following formula (1): Scattering intensity from crystalline phase / (Scattering intensity from crystalline phase + Scattering intensity from amorphous phase) … (1) Negative electrode active material layer. <Aspect 2> The negative electrode active material layer according to Aspect 1, wherein x in the aforementioned general formula is Mg. <Aspect 3> The negative electrode active material layer according to Aspect 2, wherein the aforementioned crystallinity is 1.0% or less. <Aspect 4> A solid battery having the negative electrode active material layer according to any one of Aspects 1 to 3, a solid electrolyte layer, and a positive electrode active material layer in this order. [Advantageous Effects of Invention]
[0007] According to the present disclosure, it is possible to provide a negative electrode active material layer capable of improving the discharge rate characteristics of a battery, and a solid battery having such a negative electrode active material layer. [Brief Description of Drawings]
[0008] [Figure 1] Figure 1 is a schematic cross-sectional view showing an example of the solid battery of the present disclosure. [Figure 2] Figure 2 is an XRD pattern for Li in the lithium alloy in the negative electrode active material layers of Examples 1 to 4 and Comparative Example 1 at a depth of discharge (DOD) of 80%. [Figure 3] Figure 3 is a graph showing the relationship between the crystallinity of Li in the lithium alloy in the negative electrode active material layer and the discharge capacity ratio of the battery for Examples 1 to 4 and Comparative Example 1. [Mode for Carrying Out the Invention]
[0009] Hereinafter, embodiments of the present disclosure will be described in detail. The present disclosure is not limited to the following embodiments, and can be implemented with various modifications within the scope of the gist of the disclosure.
[0010] <<Negative Electrode Active Material Layer>> The negative electrode active material layer of this disclosure comprises a lithium alloy represented by the general formula Li-X at a discharge depth of 80%, where X is Mg, Ag, or a combination thereof. In the negative electrode active material layer of this disclosure, the degree of crystallinity of Li in the lithium alloy, as determined by XRD analysis, is 8.0% or less, where the degree of crystallinity is represented by the following formula (1): Scattering intensity from the crystalline phase / (Scattering intensity from the crystalline phase + Scattering intensity from the amorphous phase) ... (1).
[0011] The Disclosing Party has found that in a negative electrode active material layer containing a lithium alloy represented as a Li-X alloy (X = Mg, Ag, or a combination thereof), the discharge capacity decreases under conditions of high current density, i.e., during rapid discharge. The reason for this is presumed to be as follows, although this is not intended to be bound by any theory: During rapid discharge, it is thought that a layer with a high concentration of Mg and / or Ag is generated due to the dissolution of Li from the interface between the lithium alloy and the electrolyte. This layer acts as a resistive layer with a low diffusion rate of Li ions, and therefore, the discharge capacity during rapid discharge decreases, i.e., the discharge rate characteristics deteriorate.
[0012] In response to this, the Disclosing Party found that the low degree of crystallinity of Li in the lithium alloy, as determined by XRD analysis, suppresses the decrease in discharge capacity during rapid discharge, and therefore improves the discharge rate characteristics. The reason for this is presumed to be as follows, although this is not intended to be constrained by any theory: In the amorphous phase, there are many diffusion pathways for Li ions, and therefore, the diffusivity of Li ions is considered to be higher in the amorphous phase than in the crystalline phase. And, as the diffusivity of lithium ions improves, Li is more easily supplied to the solid electrolyte interface, and therefore, the discharge rate characteristics are considered to be improved.
[0013] The following describes the elements that may constitute the negative electrode active material layer of this disclosure.
[0014] The negative electrode active material layer of this disclosure contains a lithium alloy represented by the general formula Li-X when the depth of discharge (DOD) is 80%, where X is Mg, Ag, or a combination thereof. In the negative electrode active material layer, the lithium alloy functions as the negative electrode active material. The depth of discharge refers to the ratio of the discharge amount to the discharge capacity of the secondary battery.
[0015] In the negative electrode active material layer of this disclosure, the degree of crystallinity of Li in the lithium alloy, as determined by XRD analysis, is 8.0% or less, where the degree of crystallinity is given by the following formula (1): Scattering intensity from the crystalline phase / (Scattering intensity from the crystalline phase + Scattering intensity from the amorphous phase) ... (1).
[0016] Thus, a lower degree of crystallinity of Li in the lithium alloy can improve the discharge rate characteristics of the battery.
[0017] In the general formula, X may be Mg or Ag, and especially Mg. This effectively improves the discharge rate characteristics of the battery.
[0018] The degree of crystallinity shown in formula (1) above may be 6.0% or less, 5.0% or less, 4.0% or less, 3.0% or less, 2.0% or less, 1.0% or less, 0.8% or less, 0.6% or less, 0.5% or less, 0.4% or less, 0.3% or less, 0.2% or less, or 0.1% or less, and may be 0% in particular. This effectively improves the discharge rate characteristics of the battery.
[0019] The degree of crystallinity can be determined as follows. First, the DOD of the solid-state battery containing the negative electrode active material layer of this disclosure is adjusted to 80%. Then, the solid-state battery is disassembled, and XRD measurement is performed on the surface of the negative electrode active material layer on the negative electrode current collector foil side. The XRD measurement can be performed by fitting the powder X-ray analysis software PDXL with a fitting range of 5° to 40° and analyzing the Li in the Li-Mg alloy. In the obtained XRD pattern, the degree of crystallinity can be calculated from the scattering intensity from the crystalline phase based on the peak originating from the Li(110) plane around 36.4° and the scattering intensity from the amorphous phase based on the baseline in the range of 5° to 40°.
[0020] The thickness of the negative electrode active material layer in this disclosure is not particularly limited and may be 30 nm to 5000 nm, 100 nm to 3000 nm, or 500 nm to 1500 nm.
[0021] The negative electrode active material layer of this disclosure may or may not contain negative electrode active materials other than the lithium alloy described above, and other optional components. The lithium alloy content in the negative electrode active material layer of this disclosure may be 50% by mass or more, 70% by mass or more, 80% by mass or more, 90% by mass or more, or 95% by mass or more, and may also be 100% by mass.
[0022] <Method for manufacturing the negative electrode active material layer> The negative electrode active material layer of this disclosure can be manufactured by a method comprising the following steps: Using an electron beam deposition apparatus, magnesium and / or silver are vacuum deposited onto the surface of the negative electrode current collector layer or the solid electrolyte layer to form a metal layer, wherein the emission current value of the electron beam deposition apparatus is 50 mA or higher; Prepare a positive electrode active material layer containing lithium-containing positive electrode active material; To fabricate a precursor battery having a negative electrode current collector layer, a metal layer, a solid electrolyte layer, and a positive electrode active material layer in this order; The precursor battery is charged to alloy lithium with the magnesium and / or silver in the metal layer.
[0023] By keeping the emission current value within the above range, the degree of crystallinity of Li in the lithium alloy can be reduced. The emission current value may be 80mA or more, 100mA or more, 120mA or more, 140mA or more, or 150mA or more, and may also be 300mA or less, 200mA or less, or 150mA or less. This effectively reduces the degree of crystallinity of Li in the lithium alloy.
[0024] The degree of Li crystallinity can also be controlled by adjusting the film deposition rate.
[0025] For electron beam deposition, the ULVAC EBX-1000C can be used.
[0026] From the viewpoint of promoting alloying of the magnesium and / or silver in the metal layer with lithium, the precursor battery may be charged and discharged multiple times. The number of charge and discharge cycles is not particularly limited and can be set appropriately considering the thickness of the metal layer, etc.
[0027] For the negative electrode current collector layer, the solid electrolyte layer, and the positive electrode active material layer, refer to the following description of the solid-state battery in this disclosure.
[0028] <<Solid battery>> The solid-state battery of this disclosure has a negative electrode active material layer, a solid electrolyte layer, and a positive electrode active material layer in this order. As illustrated in Figure 1, the solid-state battery 1 of this disclosure may have a negative electrode current collector layer 10, a negative electrode active material layer 20, a solid electrolyte layer 30, a positive electrode active material layer 40, and a positive electrode current collector layer 50 in this order.
[0029] In this disclosure, “solid-state battery” means a battery that includes at least a solid electrolyte as an electrolyte, and therefore a solid-state battery may include a combination of a solid electrolyte and a liquid electrolyte as an electrolyte. Furthermore, a solid-state battery of this disclosure may be an all-solid-state battery, i.e., a battery that includes only a solid electrolyte as an electrolyte.
[0030] The solid-state battery of this disclosure may be a solid-state rechargeable battery, and in particular may be a solid-state lithium-ion rechargeable battery.
[0031] The following describes the elements that may constitute the solid-state battery of this disclosure. The following examples illustrate the case where the solid-state battery of this disclosure is an all-solid-state lithium-ion secondary battery.
[0032] <Negative electrode current collector layer> The negative electrode current collector layer may be made of a material that does not alloy with Li, such as SUS, copper, and nickel. Examples of negative electrode current collector layer forms include foil and plate shapes. Examples of planar shapes for the negative electrode current collector layer include circular, elliptical, rectangular, and any polygonal shape. The thickness of the negative electrode current collector layer is not particularly limited and may be, for example, 1 μm to 50 μm, or 5 μm to 20 μm.
[0033] <Negative electrode active material layer> For information regarding the negative electrode active material layer, please refer to the description above.
[0034] <Solid electrolyte layer> The solid electrolyte layer comprises a solid electrolyte and optionally a binder.
[0035] The thickness of the solid electrolyte layer is not particularly limited.
[0036] (solid electrolyte) Examples of solid electrolytes include sulfide solid electrolytes and oxide-based solid electrolytes.
[0037] Examples of the sulfide solid electrolyte include Li2S-P2S5, Li2S-SiS2, LiX-Li2S-SiS2, LiX-Li2S-P2S5, LiX-Li2O-Li2S-P2S5, LiX-Li2S-P2O5, LiX-Li3PO4-P2S5, and Li3PS4. The description of the above "Li2S-P2S5" means a material formed using a raw material composition containing Li2S and P2S5, and the same applies to other descriptions. Further, "X" in the above LiX represents a halogen element. The raw material composition containing the above LiX may contain one or two or more types of LiX. When two or more types of LiX are contained, the mixing ratio is not particularly limited.
[0038] As the oxide-based solid electrolyte, Li 6.25 La3Zr2A l0.25 O 12 , Li3PO4, and Li 3+x PO 4-x N x (0<x≦3) are exemplified.
[0039] The shape and size of the solid electrolyte are not particularly limited.
[0040] The content of the solid electrolyte in the solid electrolyte layer is not particularly limited, and can be appropriately set in consideration of desired ion conductivity and the like.
[0041] (Binder) Examples of the binder include acrylonitrile butadiene rubber (ABR), butadiene rubber (BR), polyvinylidene fluoride (PVdF), and styrene butadiene rubber (SBR).
[0042] The content of the binder in the solid electrolyte layer is not particularly limited, and can be appropriately set in consideration of desired binding properties and the like.
[0043] <Protective Layer> Although not shown, the solid battery of the present disclosure may further include a protective layer containing a metal between the negative electrode active material layer and the solid electrolyte layer. Thereby, the resistance at the interface between the negative electrode active material layer and the solid electrolyte layer can be suppressed. The metal in this protective layer is not particularly limited, and may be, for example, tin.
[0044] <Positive Electrode Active Material Layer> The positive electrode active material layer contains a positive electrode active material, and may optionally contain a solid electrolyte, a conductive auxiliary agent, and a binder.
[0045] The thickness of the positive electrode active material layer is not particularly limited.
[0046] (Positive Electrode Active Material) Examples of the positive electrode active material include metallic lithium (Li), lithium alloys, LiCoO2, LiNi x Co 1-x O2 (0<x<1), LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, LiMnO2, hetero-element substituted Li-Mn spinel (for example, LiMn 1.5 Ni 0.5 O4, LiMn 1.5 Al 0.5 O4, LiMn 1.5 Mg 0.5 O4, LiMn 1.5 Co 0.5 O4, LiMn 1.5 Fe 0.5 O4, and LiMn 1.5 Zn 0.5 O4), lithium titanate (for example, Li4Ti5O 12 ), lithium metal phosphate (for example, LiFePO4, LiMnPO4, LiCoPO4, and LiNiPO4), LiCoN, Li2SiO3, and Li4SiO4 are exemplified.
[0047] Lithium alloys include Li-Au, Li-Mg, Li-Sn, Li-Si, Li-Al, Li-Ge, Li-Sb, Li-B, Li-C, Li-Ca, Li-Ga, Li-As, Li-Se, and Li-Ru. , Li-Rh, Li-Pd, Li-Ag, Li-Cd, Li-Ir, Li-Pt, Li-Hg, Li-Pb, Li-Bi, Li-Zn, Li-Tl, Li-Te, Li-At, and Li-In.
[0048] A coating layer containing a Li-ion conductive oxide may be formed on the surface of the positive electrode active material. Examples of Li-ion conductive oxides include LiNbO3 and Li4Ti5O 12 Examples include Li3PO4.
[0049] The shape and size of the positive electrode active material are not particularly limited.
[0050] The amount of positive electrode active material in the positive electrode active material layer is not particularly limited and can be set appropriately considering the desired battery capacity, etc.
[0051] (solid electrolyte) For information on solid electrolytes, please refer to the description above.
[0052] The content of the solid electrolyte in the positive electrode active material layer is not particularly limited and can be set as appropriate, taking into consideration the desired ionic conductivity, etc.
[0053] (Conductive additive) The conductive additive is not particularly limited and may be, for example, a carbon material, metal particles, or a combination thereof. The carbon material is not particularly limited and may be, for example, carbon black such as acetylene black or furnace black; fibrous carbon materials such as carbon nanotubes, carbon nanofibers, or vapor-grown carbon; or a combination thereof. The metal particles are not particularly limited and may be, for example, particles of Ni, Cu, Fe, and SUS, or a combination thereof.
[0054] The content of the conductive additive in the positive electrode active material layer is not particularly limited and can be set as appropriate, taking into consideration the desired electronic conductivity, etc.
[0055] (binder) For information about binders, please refer to the description above.
[0056] The binder content in the positive electrode active material layer is not particularly limited and can be set as appropriate, taking into consideration the desired binding properties, etc.
[0057] <Positive electrode current collector layer> The material for the positive electrode current collector layer may be a known metal usable as a current collector layer for solid-state batteries. Examples of such metals include at least one selected from the group consisting of Cu, Ni, Al, V, Au, Pt, Mg, Fe, Ti, Co, Cr, Zn, Ge, and In. Examples of positive electrode current collector layer forms include foil and mesh. The thickness of the positive electrode current collector layer is not particularly limited.
[0058] <Other configurations> The solid-state battery of this disclosure may have each of the above components housed inside an outer casing. Any known outer casing for solid-state batteries can be used. In addition, multiple solid-state batteries may be electrically connected and stacked as they are to form a battery pack. In this case, the battery pack may be housed inside a known battery case. The solid-state battery may also have other obvious components such as necessary terminals. The shape of the solid-state battery may be, for example, coin-type, laminated (pouch) type, cylindrical type, prismatic type, etc.
[0059] <Method of manufacturing solid-state batteries> The solid-state battery of this disclosure can be manufactured by a method that includes manufacturing a negative electrode active material layer in the manner described above. [Examples]
[0060] <<Example 1>> <Formation of a negative electrode active material layer containing lithium alloy> (Magnesium layer deposition) Using an electron beam deposition system (ULVAC, EBX-1000C), a 1000 nm thick magnesium (Mg) film was deposited on a nickel (Ni) foil with an emission current of 150 mA to form a Mg layer. Furthermore, using the electron beam deposition system, a 100 nm thick tin (Sn) film was deposited on the Mg layer to form a Sn layer.
[0061] (Battery construction) As a sulfide-based solid electrolyte, 101.7 mg of Li2S-P2S5 material containing LiBr and LiI was prepared, and the sulfide-based solid electrolyte was dispersed at a rate of 6 ton / cm³. 2 A solid electrolyte layer (thickness: 500 μm) was obtained by pressing with a pressure of 1 ton / cm². A metallic lithium (Li) foil (thickness: 150 μm) was placed on one side of the solid electrolyte layer, and a Ni foil with laminated Mg and Sn layers was placed on the other side so that the solid electrolyte layer and the Sn layer were in contact with each other. These were then pressed at a pressure of 1 ton / cm². 2 A battery was obtained by press molding under pressure, having a Li metal foil, a solid electrolyte layer, a Sn layer, a Mg layer, and a Ni foil in that order.
[0062] (alloying) The resulting battery was left to stand in a 25°C constant temperature bath for 1 hour to equalize the temperature inside the battery. The battery was then subjected to a current density of 435 μA / cm². 2 The battery was charged with a constant current. As the metallic Li foil dissolved during this charging, the Li that had moved through the solid electrolyte layer to the Mg layer was alloyed with the Mg in the Mg layer, forming a negative electrode active material layer containing a Li-Mg alloy. The charging capacity of the evaluation battery was 4.35 mAh / cm². 2 Charging was stopped when the target was reached. This resulted in an all-solid-state battery having a negative electrode active material layer containing a Li-Mg alloy.
[0063] <<Examples 2-4 and Comparative Example 1>> Except for changing the emission current value of the electron beam deposition apparatus as shown in Table 1, the negative electrode active material layers of Examples 2 to 4 and Comparative Example 1, as well as the all-solid-state battery, were obtained in the same manner as in Example 1.
[0064] <<Degree of Crystallinity>> After adjusting the DOD of each solid-state battery to 80%, the batteries were disassembled, and XRD measurements were performed on the surface of the Ni current collector foil side of the negative electrode active material layer. The XRD measurements were performed using powder X-ray analysis software PDXL, with a fitting range of 5° to 40°, and the analysis was performed on the Li in the Li-Mg alloy. The obtained XRD patterns are shown in Figure 2. In the XRD patterns shown in Figure 2, the degree of crystallinity was calculated from the scattering intensity from the crystalline phase based on the peak originating from the Li(110) plane around 36.4° and the scattering intensity from the amorphous phase based on the baseline in the range of 5° to 40°. The results are shown in Table 1.
[0065] <<Discharge capacity ratio>> Table 1 and Figure 3 show the discharge capacity ratios for each example of solid-state battery when discharged under specified conditions. "Discharge capacity ratio" means the discharge capacity at 1C divided by the discharge capacity at 0.2C.
[0066] [Table 1]
[0067] As shown in Table 1 and Figure 3, the batteries in the examples where the crystallinity of Li in the lithium alloy, as determined by XRD analysis, was 8.0% or less, showed a large discharge capacity ratio. In particular, the lower the crystallinity, the larger the discharge capacity ratio. [Explanation of Symbols]
[0068] 1 solid state battery 10. Negative electrode current collector layer 20 Negative electrode active material layer 30 Solid electrolyte layer 40 Cathode active material layer 50 Positive electrode current collector layer
Claims
1. At a discharge depth of 80%, the lithium alloy is represented by the general formula Li-X, where X is Mg, Ag, or a combination thereof, and The degree of crystallinity of Li in the lithium alloy, as determined by XRD analysis, is 8.0% or less, where the degree of crystallinity is given by the following formula (1): Scattering intensity from crystalline phase / (Scattering intensity from crystalline phase + Scattering intensity from amorphous phase) ... (1) Negative electrode active material layer.
2. The negative electrode active material layer according to claim 1, wherein x in the above general formula is Mg.
3. The negative electrode active material layer according to claim 2, wherein the degree of crystallinity is 1.0% or less.
4. A solid-state battery having a negative electrode active material layer, a solid electrolyte layer, and a positive electrode active material layer in that order, according to any one of claims 1 to 3.
Citation Information
Patent Citations
All-solid battery
JP2020184407A
All-solid-state battery and method for manufacturing the same
JP2024141459A